Alpha-tocopherol serum concentrations and its relationship with anthropometric, biochemical, dietary and cardiovascular risk parameters - Mota, Ana Carolina Costa Campos; da Cruz Carvalho, Maria Clara; Bona, Mariana Duarte; de Souza Marinho do Nascimento, Daniele; de Sousa, Ingrid Naihara França; de Oliveira, Priscila Gomes; de Oliveira Andrade, Eva Débora; da Silva Ribeiro, Karla Danielly; Maciel, Bruna Leal Lima (Frontiers in Nutrition, 2025)
BackgroundAlpha-tocopherol is a fat-soluble vitamin with antioxidant properties, capable of reducing oxidative stress and protecting cell membranes from oxidative damage. This vitamin also acts in the prevention of cardiovascular diseases, however research into this relationship is currently limited. This study aimed to assess the relationship between alpha-tocopherol concentrations and anthropometric, biochemical, usual dietary intake, and cardiovascular risk parameters.MethodsA cross-sectional study was conducted to collect sociodemographic, anthropometric, biochemical parameters of 92 adult individuals. Usual dietary intake was estimated with two 24-h recalls (24hR), using the Multiple Source Method. Cardiovascular risk was calculated using the Framingham global risk score (GRS). Alpha-tocopherol was examined by high performance liquid chromatography (HPLC). Multiple linear regression was used to evaluate the relationship between anthropometric, biochemical, usual dietary intake, and cardiovascular risk variables associated with alpha-tocopherol/total cholesterol concentrations.ResultsThe studied population presented a mean alpha-tocopherol of 17.80 μmol/L. Total cholesterol, non-HDL-c and LDL-c were significantly higher in individuals with higher serum concentrations of alpha-tocopherol. High-sensitivity C-reactive protein (hs-CRP) was significantly lower in subjects with higher concentrations of alpha-tocopherol. The GRS percentage was 10% for the total population. The multiple linear regression model showed that GRS was positively associated (β = 0.328; 95% CI 0.015, 0.100; p = 0.009) and the conicity index negatively associated (β = −0.290; 95% CI −8.196, −0.728; p = 0.020) with alpha-tocopherol/total cholesterol.ConclusionAlpha-tocopherol was positively associated with biochemical and cardiovascular risk parameters, suggesting metabolic alterations that are related to low-grade inflammation resulting from excess weight and increased cardiovascular risk.